FORMER PUPILS’ EXPERIENCED MENTAL HEALTH (MH) AND QUALITY OF LIFE (QOL) SOME YEARS AFTER COMPLETION OF ADAPTED SECONDARY EDUCATION - Thomassen, Gheir; Bachke, Carl Crh. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article addresses the following research question: Some years after having completed adapted secondary education, (a) how do former pupils assess their present status of MH and QoL, and (b) what aspects of the adapted education do they consider to have contributed positively to this status? The purpose of the study is to look for positive outcomes of adapted secondary education in pupils’ adult life, regarding their MH and QoL in particular. The study may also contribute knowledge that may be relevant in reducing drop-out from secondary vocational schools. Data collection was done by interviewing nine former pupils, all from the same school. Their statements were analyzed by a combination of editing analysis and quantitative content analysis. Firstly, findings show that the informants’ scored QoL of a similar level as found in other studies of the general Norwegian population. Presumably the MH is also similar. Secondly, the following aspects of the adapted secondary education are reported to contribute positively to this status: (1) The set of attitudes and relationship-building competence of the staff; (2) the good peer-milieu, and the efforts the staff invested in it; (3) the school’s well-organized program for apprenticeship and possibilities of working practically; and (4) the latter plus the modes of teaching which made the pupils achieve a feeling of coping.